Transgender individuals in Asian Islamic Countries: An overview of workplace diversity and inclusion issues in Pakistan, Bangladesh, and Malaysia - Mamun, A.A.; Heyden, M.L.M.; Yasser, Q.R. (Springer International Publishing, 2016)
Workplaces are an important dimension of social life and for helping individuals to satisfy their intrinsic needs for acceptance and belonging. In a society where gender roles are already askew, transgender individuals face particular challenges. Such challenges have been underemphasized in the diversity management literature. In this chapter we discuss empirical evidence of transgender issues and how they are perceived in Asian countries, particularly Pakistan, Bangladesh, and Malaysia. In addition, we outline the specific challenges faced by transgender individuals in the context of constitutional precincts, religious perceptions, and socio-economic circumstances. We argue and find that regulators, social actors and institutions in Asian Islamic countries de-emphasize the gender criteria when hiring, as well as in commonplace operations, to enrich the institutional human capital and, ultimately, work performance. We develop a future research agenda for informing individuals, organizational leaders, and policy makers concerning transgender issues.